1995
DOI: 10.1111/j.1464-5491.1995.tb00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Pakistan National Diabetes Survey: Prevalence of Glucose Intolerance and Associated Factors in Shikarpur, Sindh Province

Abstract: The prevalence of diabetes mellitus and impaired glucose tolerance (IGT) and their relationship to age and obesity was estimated in the rural town of Shikarpur in Sindh Province, Pakistan by a population-based survey in 1994. Oral glucose tolerance tests were performed in a stratified random sample of 967 adults (387 men, 580 women) aged 25 years and above. The diagnoses of diabetes and IGT were made on the basis of WHO criteria. The response rate was 71% for men and 80% for women. The prevalence of diabetes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 17 publications
3
56
1
Order By: Relevance
“…The National Health Survey of Pakistan (1990 to 1994) showed that one of three individuals aged 45 yr or older has hypertension. The prevalence of diabetes in South Asian countries is two-to three-fold higher than that reported for Western countries (5). The high prevalence of other chronic diseases in this population suggests that the burden of CKD is likely to be high.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The National Health Survey of Pakistan (1990 to 1994) showed that one of three individuals aged 45 yr or older has hypertension. The prevalence of diabetes in South Asian countries is two-to three-fold higher than that reported for Western countries (5). The high prevalence of other chronic diseases in this population suggests that the burden of CKD is likely to be high.…”
Section: Discussionmentioning
confidence: 60%
“…Evidence from the Western countries is emerging that migrant populations of South Asian origin have a higher risk for chronic kidney disease (CKD) than the native whites (1)(2)(3). Although no reliable data are available on the incidence and prevalence of CKD in South Asia, the burden of its risk factors, including hypertension and diabetes, in this population is one of the highest in the world (4,5). Therefore, the burden of CKD is expected to be equally high.…”
mentioning
confidence: 99%
“…Two later studies demonstrated that the risk of death and cardiovascular events in people with coronary artery disease are directly related to the degree of renal dysfunction [12,13]. The high prevalence of CKD in the population in Pakistan is not unexpected since the incidence of hypertension and diabetes in Pakistan is one of the highest in the world [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic Association of Pakistan (DAP) has contributed significantly by serving as WHO collaborating center for diabetes and was involved in conducting national diabetes surveys (10)(11)(12)(13)(14) Baqai Institute of Diabetology and Endocrinology (BIDE) was the first to give the concept of multidisciplinary care team and is the pioneer institute in the field of diabetes in Pakistan aiming to provide comprehensive and standardized diabetes care to the diabetic subjects in a resource poor environment. A collaborative study between BIDE and Diabetic association of Pakistan and WHO collaborating center (DAP), was conducted in 2007 to assess the mode of presentation and prevalence of acute and chronic complications in type 1 diabetes mellitus in Pakistan.…”
Section: Introduction:-mentioning
confidence: 99%